2014 Afghanistan Enterprise Survey : Country Highlights - World Bank Group (Washington, DC, 2014)
The World Bank interviewed a representative sample of the private sector in 5 of the most active economic regions in Afghanistan. The sample consisted of 410 business establishments surveyed from May 2013 through July 2014. The Enterprise Survey covers several topics of the business environment as well as performance measures for each firm. This provides the main highlights from the survey.